Postnatal maternal separation modifies the response to an obesogenic diet in adulthood in rats - Laura Paternain; Eva Martisova; Fermín I. Milagro; María J. Ramírez; J. Alfredo Martínez; Javier Campión (The Company of Biologists, 2012)
SUMMARY An early-life adverse environment has been implicated in the susceptibility to different diseases in adulthood, such as mental disorders, diabetes and obesity. We analyzed the effects of a high-fat sucrose (HFS) diet for 35 days in adult female rats that had experienced 180 minutes daily of maternal separation (MS) during lactancy. Changes in the obesity phenotype, biochemical profile, levels of glucocorticoid metabolism biomarkers, and the expression of different obesity- and glucocorticoid-metabolism-related genes were analyzed in periovaric adipose tissue. HFS intake increased body weight, adiposity and serum leptin levels, whereas MS decreased fat pad masses but only in rats fed an HFS diet. MS reduced insulin resistance markers but only in chow-fed rats. Corticosterone and estradiol serum levels did not change in this experimental model. A multiple gene expression analysis revealed that the expression of adiponutrin (Adpn) was increased owing to MS, and an interaction between HFS diet intake and MS was observed in the mRNA levels of leptin (Lep) and peroxisome proliferator-activated receptor gamma coactivator 1 alpha (Ppargc1a). These results revealed that early-life stress affects the response to an HFS diet later in life, and that this response can lead to phenotype and transcriptomic changes.